Proposta de implementação de ferramentas lean manufacturing em uma indústria do setor automotivo - Dopkoski, Julia (2020)
The reduction of waste in production processes through the use of lean manufacturing methodology Tools is one of the strategies of the industries to remain competitive in the market nowadays. This final paper was carried out in an automotive parts industry located at the Campos Gerais area - Paraná. It aims to propose the implementation of lean manufacturing tools, for which the production stops were evaluated, and the lack of material as the cause to be analyzed was selected using the Pareto Diagram. With the cause defined, lack of prefabricated material, the analysis was continued to identify the root causes with the use of the tools, Ishikawa Diagram, and 5W. From this, it was possible to diagnose and build an action plan to reduce downtime. The action plan proposes the surpermarket creation, using a rack and shelves with identification of the appropriate location of each piece. As well as the implementation of the Kanban board in the areas to control the inflows and outflows of internal stock and to assist in visual management improving the production schedule.